Effect of autologous concentrated growth factor on bedsore wounds in elderly patients with diabetes: a case-control study - Bao, Qin-wen; Xu, Jing; Wang, Zhi; Hu, Guangyun; Zhong, Wen; Li, Yunfeng; Dong, Xiao-lei; Xu, Tong-dao; Gao, Chong (Frontiers in Endocrinology, 2025)
BackgroundPressure ulcers, also known as bedsores, are common injuries to the skin and subcutaneous tissues in patients who are bedridden or wheelchair-bound, with a particularly high incidence among elderly patients with diabetes. These chronic wounds often lead to increased morbidity, prolonged hospitalization, and reduced quality of life. Traditional treatments for pressure ulcers have limited efficacy. In recent years, autologous concentrated growth factor (ACGF) has emerged as a promising regenerative medicine approach, showing potential in promoting wound healing through enhanced cell proliferation, accelerated angiogenesis, and improved tissue regeneration.ObjectiveThis study aims to evaluate the effectiveness of ACGF in treating pressure ulcers in elderly diabetic patients by comparing wound healing, symptom relief, and inflammatory markers with those receiving conventional therapy.MethodsThis analysis included 51 elderly patients aged 60 years or older with diabetes and pressure ulcers. Patients were divided into two groups: 26 received standard wound care (Control Group, CG), and 25 received ACGF treatment in addition to standard care (Treatment Group, TG). ACGF was prepared using a standardized protocol and applied directly to the wound site. Pain levels (VAS scores), wound healing (PUSH scores), and inflammatory markers (WBC, CRP, PCT, and IL-6) were compared between the two groups before treatment, 14 days, and 28 days after treatment.ResultsVAS Scores: Before treatment, there was no significant difference between the two groups (TG: 6.92 ± 0.86, CG: 6.69 ± 1.01, P=0.392). At 14 days post-treatment, the VAS scores in the TG were significantly lower than those in the CG (TG: 3.52 ± 0.51, CG: 4.46 ± 0.58, P<0.001). By 28 days, the VAS scores in the TG further decreased (TG: 1.24 ± 0.44, CG: 1.58 ± 0.70, P=0.046). PUSH Scores: Before treatment, there was no significant difference between the two groups (TG: 14.84 ± 1.72, CG: 14.19 ± 1.92, P=0.211). At 14 days, the TG showed a significantly lower PUSH score than the CG (TG: 6.52 ± 0.71, CG: 8.23 ± 0.77, P<0.001). By 28 days, the PUSH scores in the TG continued to decrease (TG: 2.52 ± 0.59, CG: 3.39 ± 0.50, P=0.001). Inflammatory Markers: Before treatment, there were no significant differences in WBC, CRP, PCT, and IL-6 levels between the two groups (P>0.05). At 14 days post-treatment, the TG exhibited significantly lower levels of WBC (TG: 7.44 ± 1.56, CG: 8.60 ± 1.98, P=0.024) and PCT (TG: 0.63 ± 0.45, CG: 1.29 ± 0.48, P<0.01). By 28 days, the TG also showed significant reductions in CRP (TG: 5.93 ± 9.74, CG: 18.63 ± 6.62, P<0.01) and IL-6 (TG: 3.35 ± 1.89, CG: 5.56 ± 2.22, P<0.01).ConclusionThis study suggests that ACGF is an effective adjunctive treatment for pressure ulcers in elderly diabetic patients. By significantly enhancing wound healing and reducing inflammatory responses, ACGF could serve as a valuable addition to standard care protocols for this vulnerable population. Further prospective studies are warranted to confirm these findings and explore the underlying mechanisms of ACGF in wound healing.Clinical Trial Registrationhttps://www.medicalresearch.org.cn, identifier MR-32-24-019758.